Evaluation of facial divine proportion in North Indian Population - Naseem Ahmad Khan; Amit Nagar; Pradeep Tandon; Gulshan Kumar Singh; Alka Singh (Wolters Kluwer Medknow Publications, 2016)
Objective: To evaluate the facial divine proportion and its relationship with facial attractiveness in North Indian population. Materials and Methods: For evaluation of various facial proportions, standardized frontal facial photographs of total 300 subjects between 18 and 30 years of age were obtained. Black and white copies of these photographs were presented in front of an evaluation jury for assigning scores of facial attractiveness and finally 130 attractive subjects were selected. These subjects were divided into two groups, Group I (attractive females n = 65) and Group II (attractive males n = 65) and they were further analyzed for various parameters of facial proportions. Unpaired Student's t-test was used to compare both groups. Results: Group I showed that five of seven vertical facial proportions were close to divine proportion (1.618) whereas only two vertical proportions in Group II were close to it. Transverse facial proportions in both groups deviated more from divine proportion (1.618) and were closer to silver proportion (1.414). Conclusions: Most of the facial proportions of attractive females in the North-Indian population were close to the divine proportion. Thus, facial divine proportion could be an important factor in the perception of facial attractiveness of North-Indian attractive females.